2003
DOI: 10.1097/00001648-200301000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Deaths Due to Injuries Among Employed Adults: The Effects of Socioeconomic Class

Abstract: We estimate 41% of deaths from external causes are attributable to having a SES below the top quartile (both sexes combined).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 13 publications
4
40
0
Order By: Relevance
“…Comparing the suicide mortality rate among the 25% of cohort members with the highest occupational rank to the 75% of cohort members in lower ranked occupations, the Steenland et al 40 study reported a population-attributable fraction of about 40%. The population-attributable fraction was estimated as the proportion of observed suicide deaths that would not occur if all labour force participants had experienced the ASMR for suicide of the lowest-exposure reference group.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the suicide mortality rate among the 25% of cohort members with the highest occupational rank to the 75% of cohort members in lower ranked occupations, the Steenland et al 40 study reported a population-attributable fraction of about 40%. The population-attributable fraction was estimated as the proportion of observed suicide deaths that would not occur if all labour force participants had experienced the ASMR for suicide of the lowest-exposure reference group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore these scores do more than measure occupation: they are a broad indicator of SES. The measure has been used in numerous studies linking SES and health (e.g., Meyer et al 2004;Steenland et al 2003;Steenland, Hu, and Walker 2004;Temby and Smith 2013).…”
Section: Measurementmentioning
confidence: 99%
“…In the few studies conducted, the lowest rates of homicide mortality are seen in persons with higher occupational attainment and educational credentials (the latter observation, in part, led to our examining the IQ-homicide link reported herein). [2][3][4] In our study, the same observations were made for parental occupational social class and the participants' own educational attainment by early adulthood in relation to homicide risk. The observation of a protective effect for increased height may be as much attributable to the favourable social circumstances it indexes as to the possible deterrent to violence that increased stature could confer.…”
Section: Discussionmentioning
confidence: 99%